The People's Forests. - Marshall, Robert (UPCC book collections on Project MUSE., 2002)
Devoted conservationist, environmentalist, and explorer Robert Marshall (1901-1939) was chief of the Division of Recreation and Lands, U.S. Forest Service, when he died at age thirty-eight. Throughout his short but intense life, Marshall helped catalyze the preservation of millions of wilderness acres in all parts of the U.S., inspired countless wilderness advocates, and was a pioneer in the modern environmental movement: he and seven fellow conservationists founded the Wilderness Society in 1935. First published in 1933, The People's Forests made a passionate case for the public owner.